Integrating evidence and learning for impact in AICCRA - Schuetz, Tonya; Tobon, Hector; Kikulwe, Enoch; Giombini, Valentina; Barlis, Angelica (2025)
This brief is part of the AICCRA MELIA Info Note Series, which aims to document, distill, and share key learnings from across the project’s two implementation phases—AICCRA I and the Additional Financing period. By capturing what has worked, what challenges have emerged, and how systems have adapted, this series provides critical insights to inform the design and strategic direction of the upcoming third phase of the project. The emphasis is on strengthening evidence-based implementation through lessons learned in monitoring, evaluation, learning, impact assessment, and knowledge and data sharing.